2016
DOI: 10.1108/ijsms-11-2016-020
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prior affect and sensory stimuli on motorsport spectators’ in-the-moment experiences

Abstract: Purpose The purpose of this paper is to provide meaningful information to sport organizations that have just recently started hosting sporting events in a new market and want to build long-term relationships with that market’s consumers. Design/methodology/approach Using self-administered questionnaires, the study surveys 463 spectators who attended the 2012 Formula One Korean Grand Prix. Findings Prior affect and existing sensory cues are crucial for spectators’ consumption behavior. Spectators’ prior eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…In the research of Park et al (2019), in which they examined the relationships between the brand value of the sportsman, spectator satisfaction and BI, it was concluded that the overall satisfaction level with sports events has a direct impact on re-purchasing behavior and word-of-mouth. A similar relationship was also tested in a study conducted with motorsports spectators: Chung et al (2016) tested the impact of previous experiences and emotional stimuli on the satisfaction and re-attendance of spectators who attended the Formula One Korean Grand Prix for the first time or had attended previously. In their model, it was found that satisfaction has a direct and positive impact on whether they would re-visit.…”
Section: Ijsms 212mentioning
confidence: 99%
“…In the research of Park et al (2019), in which they examined the relationships between the brand value of the sportsman, spectator satisfaction and BI, it was concluded that the overall satisfaction level with sports events has a direct impact on re-purchasing behavior and word-of-mouth. A similar relationship was also tested in a study conducted with motorsports spectators: Chung et al (2016) tested the impact of previous experiences and emotional stimuli on the satisfaction and re-attendance of spectators who attended the Formula One Korean Grand Prix for the first time or had attended previously. In their model, it was found that satisfaction has a direct and positive impact on whether they would re-visit.…”
Section: Ijsms 212mentioning
confidence: 99%
“…being excited or calm – of an individual to a stimulus (Russell et al , 1989). Sports research has identified this excitement as an antecedent of satisfaction (Chung et al , 2016). Our meta-analysis corroborated these findings, as the relationship found in eight effect sizes was positive ( r = 0.50 ), significant ( p < 0.05 ) and consistent (FSN Rosenthal = 2401; FSN Orwin = 84).…”
Section: Resultsmentioning
confidence: 99%
“…So, the results pointed out that various background characteristics related to the physical environment, contribute to a customer's overall feeling in the stadium (Yoshida and James, 2010). The visual stimulus concerns visual elements related to the environment such as colors, lighting, special features, and layout and design (Chung et al , 2016). The results indicated a positive and significant relationship ( r = 0.20 ; p < 0.001; FSN Rosenthal = 843; FSN Orwin = 46).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…visual attention) to generate sensory responses is critical (Artacho et al, 2020;Ebrahim et al, 2016;Kastenholz et al, 2020). These sensory responses express an individual's cognitive connection with a message (Chung et al, 2016;Hagtvedt, 2020;Lee et al, 2018). According to Zanon et al (2019), family businesses show visual cues, such as family names and images, to communicate their family identity through multiple communicational channels; the firm's website is one of them.…”
Section: Theoretical Framework and Hypothesis Supportmentioning
confidence: 99%